2022
DOI: 10.5114/jos.2022.122083
|View full text |Cite
|
Sign up to set email alerts
|

Fracture resistance of custom-milled CAD/CAM post and core using two different materials: an in vitro study

Abstract: Introduction: Restoration of endodontically treated teeth could be challenging for dentists, as these teeth would be biomechanically compromised at multiple levels, such as tissue components and tooth structures.Objectives: This study aimed to evaluate fracture resistance and failure modes of teeth restored with custommilled posts and cores fabricated from polyetherketoneketone, fiber-reinforced resin materials, and prefabricated fiber posts. Material and methods: Thirty mandibular premolars were used in the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…This study showed no difference in fracture resistance. Furthermore, the failure mode in the PEKK group was favorable compared to the PFPs (Ghanem et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…This study showed no difference in fracture resistance. Furthermore, the failure mode in the PEKK group was favorable compared to the PFPs (Ghanem et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…PEKK's elastic modulus is comparable to bones. There are certain following properties unique to PEKK: High impact resistance, tensile and compressive strength, and stiffness [21] , Substantial breakdown voltage [14,15] , Exceptional barrier qualities (CO2, H2S) [14][15][16] , Outstanding wear-rate and COF control (coefficient of friction), Excellent combustion resistance features, including being naturally flame-resistant and producing little smoke, minimal smoke toxicity. [17] Biological properties of PEKK: As a prospective replacement for titanium in long-term orthopedic applications, PEKK has high biocompatibility.…”
Section: Physical and Chemical Properties Of Pekkmentioning
confidence: 99%
“…Walsh WR et al [14] has tried coating PEEK with titanium as the physical property of PEEK is maintained but the surface interface would react preferably to the host. [15] But the PEEK coated with titanium has reduced bond strength which leads to failure as it causes wear debris. That is why the PEKK is considered superior to these biomaterials.…”
Section: Introductionmentioning
confidence: 99%